You want to patent life? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Details have emerged of the position of African countries on the proposed ADPIC agreement on aspects of intellectual property rights, which should have been debated at the meeting of the World Trade Organisation in Seattle in December 1999. They...